A FIRST COMPOSITIONAL ATTEMPT INTO THE WORLD OF SILENT SHORT FILMS – SANCTUARY BY NELIO COSTA (WITH MUSIC BY ŞERBAN MARCU) - Şerban MARCU (Studia Universitatis Babeş-Bolyai. Musica)
This paper presents the author's first attempt at writing film music. The film under discussion is Sanctuary, a silent short film produced by Nelio Costa, Professor of film journalism at the UNA University Center in Belo Horizonte, Brazil. The study highlights the suggestions that the composer derived from the film, the musical solutions the composer came up with in order to “counterpoint” the visual discourse and the context in which the film was presented, at the 2nd edition of the InnerSound International New Arts Festival, in Bucharest, 2013.